Analysis of students mathematics communication ability based on Keirsey personality type through accelerated learning model - Wulansari, Indah; Walid, Walid (Department of Mathematics, Universitas Negeri Semarang, 2021)
Mathematics communication ability needs to be improved so that students can solve math problems well. The purpose of this research was to: (1) determine whether the average students' mathematics communication ability are taught using Accelerated Learning (AL) model reached 65 and finished the classical; (2) describe the mathematics communication ability of students based on personality types Keirsey through the AL model. This research method using mixed methods with sequential explanatory design. Sampling with cluster random sampling technique, the determination of the subject by using purposive sampling. The population in this study is a class VIII student in one of the Junior High Schools in Semarang by taking a class sample. The results showed that the average students' mathematics communication ability are taught using a model of the AL reached 65 and completed the classical with the percentage reached 75%. Description of mathematics communication abilities of students based on Keirsey personality types: (a) Artisan students able to two indicators; (b) Guardian students able to two indicators; (c) Idealist students able to two indicators; and (d) Rational students able to two indicators.